2015
DOI: 10.1016/j.jth.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Choice of commuting mode among employees: Do home neighborhood environment, worksite neighborhood environment, and worksite policy and supports matter?

Abstract: Background Promoting the use of public transit and active transport (walking and cycling) instead of car driving is an appealing strategy to increase overall physical activity. Purpose To quantify the combined associations between self-reported home and worksite neighborhood environments, worksite support and policies, and employees’ commuting modes. Method Between 2012 and 2013, participants residing in four Missouri metropolitan areas were interviewed via telephone (n = 1,338) and provided information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 38 publications
8
30
0
Order By: Relevance
“…NEWS item scoring and subscale score calculations followed the NEWS-Adult scoring scheme recommended by the IPEN study protocol. 52,53,139 Four-point Likert-type scale response options for all NEWS-India items ranging from 1 (strongly agree) to 4 (strongly disagree) were combined as "agree" (strongly agree, agree) and "disagree" (disagree, strongly disagree). All NEWS-India items were positively scored to ensure that a higher score denotes a more walkable/activity-friendly neighborhood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NEWS item scoring and subscale score calculations followed the NEWS-Adult scoring scheme recommended by the IPEN study protocol. 52,53,139 Four-point Likert-type scale response options for all NEWS-India items ranging from 1 (strongly agree) to 4 (strongly disagree) were combined as "agree" (strongly agree, agree) and "disagree" (disagree, strongly disagree). All NEWS-India items were positively scored to ensure that a higher score denotes a more walkable/activity-friendly neighborhood.…”
Section: Discussionmentioning
confidence: 99%
“…11,24,40,49 Studies have consistently found associations between mixed land-use neighborhoods, reduced motor vehicle use, increases in walking, bicycling, and transit use, and a lower likelihood of obesity among residents. 24,47,[50][51][52][53] However, studies examining PA and BE associations thus far have been primarily limited to North America, Europe, Australia, and South America. [54][55][56] Findings from these studies may not generalize to other parts of the world, particularly LMICs like India where populations face a higher NCD risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adams et al (2016) found that the perception of a walkable environment around the workplace stimulates higher levels of active commuting. Yang et al (2015) investigated the combination of spatial variables and worksite incentives. Free or discounted PT tickets and recreational facilities at the worksite had the greatest effect on PT use and active mobility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is abundant research documenting environmental factors that influence AC participation, including having a shorter commute, living in a neighborhood with connected streets, and worksite supports (e.g. schedule, showers, locker rooms, bike parking) [17,27,28,29,30]. It is important to acknowledge the factors that prevent or motivate adults to AC to further intervene on this behavior in the future.…”
Section: Introductionmentioning
confidence: 99%